2(x-2)+3x=2(x+1)-12

Simple and best practice solution for 2(x-2)+3x=2(x+1)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-2)+3x=2(x+1)-12 equation:



2(x-2)+3x=2(x+1)-12
We move all terms to the left:
2(x-2)+3x-(2(x+1)-12)=0
We add all the numbers together, and all the variables
3x+2(x-2)-(2(x+1)-12)=0
We multiply parentheses
3x+2x-(2(x+1)-12)-4=0
We calculate terms in parentheses: -(2(x+1)-12), so:
2(x+1)-12
We multiply parentheses
2x+2-12
We add all the numbers together, and all the variables
2x-10
Back to the equation:
-(2x-10)
We add all the numbers together, and all the variables
5x-(2x-10)-4=0
We get rid of parentheses
5x-2x+10-4=0
We add all the numbers together, and all the variables
3x+6=0
We move all terms containing x to the left, all other terms to the right
3x=-6
x=-6/3
x=-2

See similar equations:

| X+6x-9=40 | | 8-8(1+3x)=4-2x | | 3m2= −16m − 21 | | -(3-12b)=5 | | 21+3n+12=0 | | 7(x+2)+7=7x+6 | | -8x-10x+60+100=80+6x+20+10x | | 7/3+3m/7=61/21 | | d+(2/3)=-3/4 | | 2y+85=75 | | d+2/3=-3/4 | | 9p-18=17 | | 76-14y=56 | | 3y+2y-5+10=20 | | 12x+23+2x+3=180 | | x/42+x/42=49/42 | | 19+5b=12-3b-17 | | 18x=405 | | 4y/5=7/15-3 | | 5x^2+160=0 | | 1/3x+20+x+5=33 | | 8t+30+2t-16=-22 | | w-39=7 | | 13+3p+10=23-3p | | 40=4d+8 | | 2.5p-14=8p+4 | | Y=-3/4x+15 | | 4y+7=10+6y | | 21(2-y)+12y=44 | | 4x-4x-18=-18 | | N+8=9n+72 | | m-2,25=4,50 |

Equations solver categories